Techniques of Using Intertextuality and Lecturer-Students’ Power Relation when Communicating Learning Tasks - Yelfiza, Yelfiza; Yulmiati, Yulmiati; Afriyanti, Rika; Sukandi, Syayid Sandi (AT-TA'LIM, 2020)
Considering the students’ emotion is essential in having the students to learn. Most Minangkabaunese students do not like being dictated for any activities with a thousand words. This paper is aimed at finding out some techniques of using intertextuality to balance lecturer-students’ power relations when communicating learning tasks. This research is qualitative with content analysis. Data were collected from six lecturers, teaching at Sekolah Tinggi Keguruandan Ilmu Pendidikan, Persatuan Guru Republik Indonesia (STKIP PGRI), selected purposively. Techniques of observation and video recording were used in collecting data. The discourse was transcribed and categorized into some techniques of using examples based on the content called content analysis.A contextual analysis was used to show lecturer-students’ power relations and formulated proposition.   Findings show that the techniques of using intertextuality includeShowing Techniques of Doing Tasks (STDT), Giving Example of the Task Topic (GETT), and UERS. Using STDT  had an impact on students’ readiness to learn. Meanwhile, Using GETT enhances students’ language development. Finally, Using Example of Real Situations (UERS)  gives students’ opportunity to have a learning experience. Moreover, the techniquescause the lecturer and students to have a balanced power relation. The findings are significant for teachers or lecturers as guidance to communicate with students efficiently and effectively. They are expected not to dominate communication when interacting with them, especially to those who have excessive individualism. Other researchers who are interested in studying this topic are expected to be inspired to research this area viewed from other viewpoints.